2011
DOI: 10.1002/app.34271
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of synthesis and characterization of cassava starch‐graft‐poly(acrylonitrile) using response surface methodology

Abstract: Graft copolymerization of poly(acrylonitrile) onto cassava starch was carried out with potassium persulphate (PPS) as the free radical initiator using a response surface Box-Behnken design. Different levels of monomer concentration, initiator concentration, and temperature were used, and regression models were generated in terms of these factors, which can be used to predict the grafting level and efficiency at a given level of the factors. The grafted starches were characterized by FTIR, XRD, and SEM analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
5
4
0
Order By: Relevance
“…The XRD patterns of representative samples, S4 and S9, are shown in Figure . This result was consistent with earlier reports by Jyothi et al . Aged thermoplastic maize starch–zein blends were reported to produce similar types of XRD patterns due to the crystallization of the short outer chains of amylopectin .…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The XRD patterns of representative samples, S4 and S9, are shown in Figure . This result was consistent with earlier reports by Jyothi et al . Aged thermoplastic maize starch–zein blends were reported to produce similar types of XRD patterns due to the crystallization of the short outer chains of amylopectin .…”
Section: Resultssupporting
confidence: 93%
“…The concentration of acrylonitrile used for the synthesis of the graft copolymer was found to have a significant positive effect on nitrogen content. Similar result was reported earlier also …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The Tm of native cassava starch in this study having about 10-13% moisture was 139°C as shown in Figure 1 below. It has been reported elsewhere that the Tm of cassava starch with 8-10% moisture content was found to be 162°C [28,29]. Reports from separate study indicated that the glass transition temperature of native cassava starch which was 139°C has decreased during solution state enzymatic esterification with recovered coconut oil [18].…”
Section: Differential Scanning Calorimetric (Dsc) Analysismentioning
confidence: 92%